Leadership Styles and Staff Productivity in Selected Tertiary Institutions in Kwara State - Dauda, Rafat Bukola (International Journal of Educational Management, 2025)
This study was carried out to determine the leadership styles and staff productivity in selected tertiary institutions in Kwara state. The study adopted a survey research design and a self-designed but validated questionnaire was used to collect the data. The population of the study was made up of chief executives of tertiary institutions in Kwara state. The collected data were subjected to statistical analysis. The two research questions were answered using mean scores and ranking order, while the null hypothesis was tested using Pearson product moment correlation statistics. The findings of the study revealed that, the leadership styles of Chief Executive of tertiary institutions in Kwara state has significant relationship with staff productivity. The leadership style mostly used by heads of tertiary institutions in Kwara state are: autocratic, democratic and laissez faire leadership styles respectively. The level of staff productivity in tertiary institution in Kwara state is high. The study concluded that the leadership styles exhibited by Chief executives of tertiary institutions in wara have strong influence on productivity. Finally, the study suggested that government at all levels (Federal, state and local) should urgently organize continuous trainings, workshops and seminars that would expose the Chief executives of tertiary institutions to modern transformational leadership styles.